2019
DOI: 10.1111/btp.12707
|View full text |Cite
|
Sign up to set email alerts
|

Changing ecological communities along an elevation gradient in seasonally dry tropical forest on Hispaniola (Sierra Martín García, Dominican Republic)

Abstract: We report the results of systematic vascular plant and bird surveys in Seasonally Dry Tropical Forest (SDTF) across leeward and windward elevation gradients (31–884 masl) in the Sierra Martín García (SMG), Dominican Republic. We expected to see gradual, systematic changes in plant distributions with elevation owing to the strong effect of topoclimate. In contrast, we predicted bird community composition to be related only weakly to elevation, because we expected bird distributions to be more strongly related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 83 publications
(110 reference statements)
1
4
0
1
Order By: Relevance
“…We detected ZD more frequently and in higher abundance at camera-trap survey locations that were dominated by flooded forest and dry forest, thus confirming previous observations [32,101,102]. In addition, Model 4 (∆AICc = 2.18) suggested that elevation had a marginal negative influence on the abundance of ZD, confirming recent observations on Hispaniola [103]. Conversely, we observed BQD more often in the tropical rainforest habitat, as previously reported [28].…”
Section: Discussionsupporting
confidence: 90%
“…We detected ZD more frequently and in higher abundance at camera-trap survey locations that were dominated by flooded forest and dry forest, thus confirming previous observations [32,101,102]. In addition, Model 4 (∆AICc = 2.18) suggested that elevation had a marginal negative influence on the abundance of ZD, confirming recent observations on Hispaniola [103]. Conversely, we observed BQD more often in the tropical rainforest habitat, as previously reported [28].…”
Section: Discussionsupporting
confidence: 90%
“…The clearing of forest in the tropics is often concentrated at lower elevation habitats, leading to the loss of specific vegetation types and their associated bird assemblages (Franklin et al, 2019;Harris et al, 2014) Although birds have been the focus of many land use change studies worldwide, research coverage in the Afrotropics remains poor and is dominated by the evaluation of taxonomic diversity, which is not always sufficiently informative about ecosystem processes and responses to environmental disturbances (Cadotte et al, 2011;Mouillot et al, 2013;Petchey & Gaston, 2002;Walker et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the removal of mature trees (large and tall) affects canopy foragers and cavity nesters (Bonaparte et al., 2020; Lindenmayer, 2017), while changes in microclimatic and edaphic conditions, such as soil water content, affect the abundance of soil invertebrates, which avian insectivores consume (Cifuentes‐Croquevielle et al., 2020; Sutherland & Green, 2004). The clearing of forest in the tropics is often concentrated at lower elevation habitats, leading to the loss of specific vegetation types and their associated bird assemblages (Franklin et al., 2019; Harris et al., 2014). For example, (a) in the montane rainforests of Rwanda, Neate‐Clegg et al (2020) reported the upslope shift of bird communities following anthropogenic habitat transformation over 15 years in Nyungwe National Park, while (b) in the Volcanoes National Park, Rwanda, where the vegetation stratification is well marked, extirpation of bird species such as Cercococcyx montanus (Barred long‐tailed cuckoo) was documented after the clearance of the low‐elevation mixed forest (Vande weghe & Vande weghe, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This provides excellent understanding of how biodiversity is impacted by individual drivers such as along temperature, precipitation or latitudinal gradients (Fitzpatrick et al, 2013;Franklin et al, 2019;Ibanez et al, 2018). However, environmental gradients are multivariate; multiple drivers of biodiversity change operate together.…”
Section: Introductionmentioning
confidence: 99%
“…While there is a large body of literature highlighting the role that spatial scale can play in shaping biodiversity patterns, they tend to focus on a single driver of diversity change. This provides excellent understanding of how biodiversity is impacted by individual drivers such as along temperature, precipitation or latitudinal gradients (Fitzpatrick et al, 2013; Franklin et al, 2019; Ibanez et al, 2018). However, environmental gradients are multivariate; multiple drivers of biodiversity change operate together.…”
Section: Introductionmentioning
confidence: 99%